Chinese Hospital Executive Professional Management Competency, Role Pressures, Personal and Organizational Performance: A Qualitative Study - Yang, Xia; Simaens, A.; Xia, Weidong; Shi, Ge (32nd EBES Conference, 2020)
In recent years, the Chinese health care market has shifted from all hospitals being government budgeted public hospitals to a mixed set of public and private health providers. The public hospitals have been forced to compete in the market with little government funding support. There have been increasing pressures for hospital executives to shift from managing hospitals based on government planning and control to managing hospitals based on professional management competences. Yes, most hospital executive positions in China have traditionally be occupied by clinical experts. Hospital executives have struggled with managing the dual-career paths that they carry simultaneously on their shoulders. On one hand, they need to continue clinical practices and development to maintain their medical expertise and credentials. On the other hand, they must adjust their mindset and gain professional management competency that are required to direct and manage their hospitals, both strategically and operationally, in the increasingly diverse and competitive market. As a result, a common challenge that Chinese hospital executives have been facing is how to gain the appropriate professional management competency and manage the role pressures in order to achieve desired performance levels, both personally and organizationally. There has been a lack of research that address these issues. To bridge this gap, we conducted a qualitative study to understand what constitute professional competency of Chinese hospital executives, what are its determinants and consequences. We conducted interviews with ten top executives from a diverse set of hospitals that represented public and private, large, medium and small hospitals. Based on the interview results, we conceptualize the key dimensions of, as well as relationships among, (1) professional management competency, (2) role pressures, and (3) personal and organizational performance of Chinese hospital executives. Implications of our study results to the theoretical literature and management practices, as well as limitations and future research directions are discussed.